Risk Factors of Work Fatigue among Transport Workers in Kupang Traditional Market, East Nusa Tenggara - Yufliyati Yuliana Lona; Anderias Umbu Roga; Eryc Z. Haba Bunga (Journal of Health Promotion and Behavior, 2023)
Background: Transport workers are jobs that need attention because the work process, they carry out carries health risks such as work fatigue. Work fatigue needs to be considered in all types of work, both formal and informal, because it causes a decrease in process efficiency, work performance and reduced physical strength or endurance which can significantly affect the health of the workforce and reduce work productivity. Work fatigue is caused by various factors, namely individual factors consisting of age, gender, and education. The work factor consists of workload. Environmental factors consist of heat stress. This study aimed to find out the risk factors for work fatigue in transport workers at the Kupang City Traditional Market in 2022. Subjects and Method: A cross-sectional study was conducted at Kupang City Market from July to August in 2022. A total of 72 subjects were included in this study. The dependent variable is work fatigue. The independent variables are workload and heat stress. Data were obtained using questionnaire and analyzed using the Chi-square test. Results: Workload (OR= 6.01; 95% CI= 2.09 to 17.28; p= 0.001) and heat stress (OR= 45.0; 95% CI= 5.37 to 376.97; p<0.001) are statistically significant associated with fatigue among transport workers. Conclusion: Workload and heat stress have a relationship with work fatigue in porters.